PENGARUH RELIGIUSITAS DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN PADA PT. BANK PERKREDITAN RAKYAT LENGAYANG CABANG KAMBANG - Erix Syahputra Deswandi; Maizul Rahmizal (LP2M Universitas Bina Bangsa, 2022)
This study aims to examine the effect of religiosity and job satisfaction on employee turnover intention at PT. Rural Bank Lengayang Kambang Branch. The population in this study were all employees at PT. Rural Bank Lengayang Branch Kambang as many as 43 people. The data collected by the total sampling method and the sampling results obtained were 43 samples. The analytical technique used is descriptive analysis (TCR). The results showed that religiosity had a positive and significant effect on employee turnover intention at PT. Rural Bank Lengayang Kambang Branch and job satisfaction have a positive and significant effect on the Turnover Intention of employees at PT. Rural Bank Lengayang Kambang Branch